Application of Project Based Learning Model to Increase Student Learning Activity - Izza Afkarina; Kholilur Rohman; Vina Rohmatul Ummah (EDUCARE: Jurnal Ilmu Pendidikan, 2023)
This study aims to determine how the implementation of the Project Based Learning model can improve students' learning activities in the subject of Islamic Cultural History. The method used in this study is qualitative with a case study approach. The subjects of the study were grade X students. Data collection techniques include observation, interviews, and documentation. Data were analyzed descriptively through the stages of data reduction, data presentation, and drawing conclusions. The results of the study indicate that the implementation of the Project Based Learning model can significantly improve students' learning activities. This is indicated by the increasing involvement of students in various stages of learning, starting from project planning, group discussions, information searches, to presentations of work results. Students become more enthusiastic, actively ask questions, discuss, and are able to develop creative solutions to learning tasks. The implication of this study is the importance of the role of teachers as facilitators in creating active and meaningful learning. The implementation of the Project Based Learning model is able to create a fun learning environment and motivate students to be directly involved in the learning process. These results are expected to encourage educators to adopt a similar approach in improving the quality of learning in various other subjects.